Synthesis and DFT Calculation of a New Series of Enaminones based on 3-amino Coumarin - Pegah Nouraie; Shahram Moradi Dehaghi; Alireza Foroumadi (Journal of Sciences, Islamic Republic of Iran)
In this paper, the synthesis of various enaminones from the reaction of 3-aminocoumarin and ethyl-2,4-dioxo-4-arylbutanoate in the presence of p-toluene sulfonic acid is reported. The reaction was examined under different solvents and catalytic systems, which clearly proved the importance of acidic catalyst in this organic transformation. This work was also accompanied by density functional theory (DFT) studies to justify the formation of final products.